Observations on the Composition and Diversity of Ant Communities in Different Habitats in a Campus Ecosystem - Swapna, S.; Athira, R.P.; Adarsh, A.S.; Parvathy, S.; Solih, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Ants are more sensitive to ecosystem changes and their fast response to habitat alterations enable them as a useful tool for natural areas restoration efforts. A preliminary investigation was conducted to determine the diversity and distribution of ants from various habitats selected across the campus of Sree Narayana College, Thiruvananthapuram, Kerala State. A total of seventeen species belonging to four subfamilies, fourteen genera and 234 individuals were collected. The subfamily Myrmicinae is the most diverse followed by Formicinae, Ponerinae and Dolichoderinae. In the present study, Diversity Index, Dominance index and Evenness index of ant species were determined. Diversity varied from 0.49 to 0.82 indicating low diversity. Dominance index value ranged from 0.17 to 0.47 while Evenness index value from 0.63 to 0.92. The results showed low diversity and dominance of ant species in the campus area indicating the severity of human interference in the campus ecosystem.